ANALISIS PNERAPAN FUNGSI CONTROLLING MANAJEMEN PERPUSTAKAAN DALAM MEWUJUDKAN VISI DAN MISI PERPUSTAKAAN SMK NEGERI 2 PONTIANAK - Pipin, Ilmuminata; Sahidi , Sahidi; Saman Madeten , Sisilya (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2025)
Every library must have a vision and mission that adapts to its parent institution. Efforts to achieve the vision and mission must of course implement management functions, one of the management functions that must be implemented is the controlling function. This research aims to describe the application of the controlling function in realizing the vision and mission and determine the obstacles in realizing the library's vision and mission. This research used descriptive qualitative methods with indirect observation techniques and in-depth interviews with 5 informants. Data analysis techniques use data reduction, verification and conclusions, while testing data validity by extending observations, increasing persistence, triangulation, negative case analysis. The results of this research show that the library of SMK Negeri 2 Pontianak has implemented a controlling function. The implementation of several controlling functions has gone well. However, the application of the controlling function to comparative analysis and feedback evaluation indicators has not been optimal. Obstacles in realizing the library's vision and mission are also caused by problems with library facilities, inadequate physical space and minimal lighting.